Boundary scavenging at the East Atlantic margin does not negate use of 231Pa/230Th to trace Atlantic overturning - Lippold, Jörg (Earth and planetary science letters, 2012)
The 231Pa/230Th method is a promising tool to reconstruct Ocean circulation over the past Glacial-Interglacial cycle. However, marine particle flux may constrain the applicability of this ratio as a direct quantitative proxy for the strength of Atlantic Meridional Overturning Circulation (AMOC) by influencing the fractionation between the in situ produced 231Pa and 230Th in ocean water.
Im Titel sind 231 und 230 hochgestellt
Gesehen am 20.11.2018